Influence of different types of sterile cytoplasms (A3, A4, 9E) on the combining ability of CMS lines of sorghum - O. P. Kibalnik; L. A. Elkonin (Вавиловский журнал генетики и селекции)
Investigation of the effect of the cytoplasm on the combining ability (CA) of lines with cytoplasmic male sterility (CMS) is of considerable interest in terms of understanding the genetic functions of the cytoplasm and for practical purposes to create hybrids with improved economically valuable traits. In order to investigate the effect of different types of sterile cytoplasm (A3, A4, 9E) on CA in sorghum, we studied the manifestation of a number of biological and agronomic traits in 54 F1 hybrid combinations obtained using iso-nuclear CMS lines with the nuclear genome of the line Zheltozernoye 10, differing only in the types of sterile cytoplasm (A3, A4 and 9E). Eighteen varieties and lines of grain sorghum developed at the Russian Research and Project-technological Institute of Sorghum and Maize were used as paternal parents. The CA was determined by the topcross method. F1 hybrids and their parents were grown in 2015–2017 in conditions of insufficient (2015–2016: HTC (hydro-thermal coefficient) = 0.32–0.66), or good water availability conditions (2017: HTC = 1.00). On average, for three years of testing, a positive effect of the 9E cytoplasm on the general combining ability (GCA) (0.63) and negative effects of the A3 and A4 cytoplasms (–0.32 and –0.31) for the inflorescence length were noted. In dry seasons, significant positive effects of the 9E cytoplasm on GCA for the length of the largest leaf, and positive effects of the A3 cytoplasm on GCA for the plant height, and negative effects of the A4 cytoplasm on GCA for these traits were observed. No differences were observed during the wet season. The type of CMS did not affect the GCA for the width of the largest leaf and grain yield. The dispersion of specific combining ability (SCA) in the dry seasons was significant for the following traits: leaf length, plant height, panicle length and width, and grain yield, the 9E cytoplasm had the highest SCA dispersion, whereas the A4 cytoplasm had the smallest one. The data obtained indicate that different types of sterile cytoplasm of sorghum make a different contribution to CA under conditions of drought stress.